PENGARUH PENGGUNAAN VIDEO ANIMASI DUA DIMENSI TERHADAP KEMAMPUAN MENGENAL ANGKA PADA ANAK USIA DINI DI TK AISYIYAH 14 PADANG - Auliza, Della; Rakimahwati; Utoyo, Setiyo; Syafnita, Tisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low ability of early childhood students in recognizing numbers at TK Aisyiyah 14 Padang, as indicated by many children who are not yet able to mention, identify, and match number symbols with the correct quantity of objects. This problem is caused by the limited use of learning media, which tends to be less attractive, making children easily bored and less actively involved in the learning process. Therefore, this study aims to determine the effect of using two-dimensional animated videos on children's ability to recognize numbers. This study employed a quantitative method with an experimental design using pre-test and post-test in both experimental and control groups. The results showed that there was a significant improvement in the number recognition ability of children in the experimental class after being given treatment using two-dimensional animated videos compared to the control class that used conventional methods. Thus, it can be concluded that the use of two-dimensional animated videos has a significant effect on improving early childhood number recognition ability at TK Aisyiyah 14 Padang.